Effect of Bacillus amyloliquefaciens and Pseudomonas migulae on the growth of gooseberry (Physalis peruviana L.) seedlings - Beltrán-Acosta, Camilo Rubén (2022)
Introduction. Using plant growth-promoting bacteria is an alternative to integrate into cape gooseberry crop management strategies, through its application in seedling stages, in order to obtain more vigorous seedlings that can tolerate biotic and abiotic stresses under field conditions. Objective. To evaluate the plant growth-promoting activity and endophytic capacity of the rhizobacteria Bacillus amyloliquefaciens Bs006 and Pseudomonas migulae Pf014 inoculated during the seedling stage of cape gooseberry (Physalis peruviana L.). Materials and methods. An experiment was carried out from April to May 2018, in a greenhouse located at the Tibaitatá Research Center, Mosquera, Colombia, with a randomized complete block design and three replications. The rhizobacteria were inoculated individually in the substrate at a concentration of 1 x 108 CFU/mL and were quantified as response variables: dry biomass (g) of root, stem, and leaves, height (cm), leaf area (cm2), and number of leaves, and their endophytism was verified by evaluating the colonization of plant tissue. Results. B. amyloliquefaciens Bs006 stimulated the growth of cape gooseberry seedlings with respect to the control. It showed greater promotion capacity than P. migulae Pf014, since it increased the length of the plant by 34 %, the stem and root growth by 59% and 16 %, respectively. It increased root dry biomass of the root by 178 %, stem by 161 %, and leaves by 96 %. Bs006 was isolated from the interior of the plant tissue, which indicates its capacity as an endophyte in cape gooseberry. Conclusions. The positive response in all the agronomic variables evaluated with the application of B. amyloliquefaciens Bs006 indicates that this bacterium can be validated during the seedling stage of cape gooseberry.